Pengenalan Teknologi Filtrasi Bertekanan Ultra Rendah kepada Santri Pondok Pesantren Ad-Diinul Qayyim Kabupaten Lombok Barat - Ahmadi, Ahmadi; Nufida, Baiq Asma; Indah, Dahlia Rosma; Bilad, Muhammad Roil; Khery, Yusran; Harisanti, Baiq Muli; Ariani, Dwi; Mesarah, Siti; Astuti, Mei Dwi; Rahma, Arinda Yusfika; Suhartini, Sriyanti (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2022)
Water treatment training using ultra-low pressure membrane filtration devices at the Ad-Diinul Qayyim Islamic Boarding School, Gunungsari Village, Gunungsari District, West Lombok Regency is an activity that aims to downstream the innovations of lecturers and students in higher education to the community, and increase public awareness about use of clean water. This activity was carried out with the stages of making a prototype filtration device, debriefing students, coordinating and socializing, implementing training, monitoring, and evaluating. The activity was carried out in the Hall of the Ad-Diinul Qayyim Islamic Boarding School and involved 30 students as participants. Activities were monitored using a training participant response questionnaire. The monitoring results showed that 86.67% of the participants understood how to use and maintain the prototype ultra-low pressure membrane filtration device. As many as 82.25% of participants agreed that learning about filtration equipment was very interesting to present in science learning. As many as 73.33% of participants agreed that the prototype of the filtration device was easy to develop.